2017
DOI: 10.1016/j.ipej.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Lead related complications in quadripolar versus bipolar left ventricular leads

Abstract: BackgroundQuadripolar left ventricular (LV) leads are capable of pacing from four different electrodes which allows for easier and more stable intra-operative lead positioning with optimal pacing parameters. We therefore investigated the rate of combined intra-operative and post-operative LV lead related events in quadripolar vs. bipolar LV lead cardiac resynchronization therapy (CRT) recipients in the real world setting.MethodsWe retrospectively collected data for N = 1441 patients at our institution implante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…A recent retrospective study comparing QUAD with bipolar leads showed no difference in survival at 12 months (mean follow-up 256 days for QUAD). 15 In contrast, a US-wide study based on data from device implant records and telemonitoring showed that CRT-D using QUAD was associated with a better survival than CRT-D using bipolar leads. 13 Observational data from 3 centers in the United Kingdom showed similar findings.…”
Section: Mortalitymentioning
confidence: 96%
See 1 more Smart Citation
“…A recent retrospective study comparing QUAD with bipolar leads showed no difference in survival at 12 months (mean follow-up 256 days for QUAD). 15 In contrast, a US-wide study based on data from device implant records and telemonitoring showed that CRT-D using QUAD was associated with a better survival than CRT-D using bipolar leads. 13 Observational data from 3 centers in the United Kingdom showed similar findings.…”
Section: Mortalitymentioning
confidence: 96%
“…11,12 Some observational studies have suggested that CRT-D using QUAD programmed to single-site LV pacing also improves survival. [12][13][14] These findings, however, are not consistent, 15 and there is uncertainty as to whether they also apply to CRT-P. Moreover, the possible influence of HF etiology and the effects of QUAD on HF hospitalization and mode of death remain largely unexplored.…”
mentioning
confidence: 99%
“…reported an overall 9% dislodgement rate with various LV lead types (bipolar, quadripolar, and active fixation leads), with a 4.8% rate for LV lead dislodgement required a re-operation. In 2017, a 2.1% vs. 3.0% dislodgement rate for quadripolar vs. bipolar CS leads was reported by Rijal et al 26 . Kassai et al 18 .…”
Section: Discussionmentioning
confidence: 89%
“…Quadripolar LV leads offer many extra pacing options than bipolar LV leads [23] , reducing the need for compromise among positional stability, phrenic nerve stimulation and capture threshold, and are associated with fewer complications [24] , [25] , [26] , [27] . In this case, the proximal 2 electrodes of the quadripolar lead in the MCV provided pacing while the distal 2 electrodes provided anchorage.…”
Section: Discussionmentioning
confidence: 99%